Selection of Saccharomyces cerevisiae Strains Applied to the Production of Prieto Picudo Rosé Wines with a Different Aromatic Profile - Álvarez-Pérez, J.M.; Álvarez-Rodríguez, M.L.; Campo, E.; Sáenz de Miera, L.E.; Ferreira, V.; Hernández-Orte, P.; Garzón-Jimeno, E.; Coque, J.J.R. (South African Journal of Enology and Viticulture, 2016)
The aim of this work was to select indigenous Saccharomyces cerevisiae strains based on a combination of genetic and aroma analyses to be used for inoculation in industrial fermentations and produce rosé wine with a different aromatic profile. A total of 118 indigenous strains of S. cerevisiae and one hybrid strain from five wineries and three different vintages were isolated from spontaneous microfermentations and genetically characterised according to the restriction fragment length polymorphism of their mitochondrial DNA (RFLP-mtDNA). From this group, 30 strains were subjected to phenotypic/oenological characterisation and, of these, nine were chosen as starters in wine fermentations due to their ability to ferment well and their appearance in consecutive vintages or in two or more wineries. Wines produced by these nine selected strains were aromatically and chemically characterised, revealing great differences in their sensory profiles. One of these strains (C9-I) showed the most complex aroma profile in the sensory characterisation, so it was selected to produce an industrial wine. A principal component analysis showed that the industrial wine produced was aromatically very different from several commercial wines produced by different wineries. In fact, their main aromatic attributes were not found in the commercial rosé wines selected for the sensory evaluation. The study shows that a combination of microbiological and chemical techniques can be an effective tool to improve the winemaking process to produce industrial wines with a distinctive organoleptic profile.